Hospital‐ and county‐level characteristics explain geographic variability in prices of cancer‐related procedures: Implications for policy and interventions - Jennifer L. Moss; Savanna G. Ledford; Veronica Bernacchi; Chan Shen (Cancer Medicine, 2024)
Abstract Background Healthcare costs in the U.S. are high and variable, which can hinder access and impact health outcomes across communities. This study examined hospital‐ and county‐level characteristics to identify factors that explain geographic variation in prices for four cancer‐related procedures. Methods Data sources included Turquoise Health, which compiles publicly‐available price data from U.S. hospitals. We examined list prices for four procedures: abdominal ultrasound, diagnostic colonoscopy, brain MRI, and pelvis CT scan, which we linked to characteristics of hospitals (e.g., number of beds) and counties (e.g., metropolitan status). We used multilevel linear regression models to assess multivariable relationships between prices and hospital‐ and county‐level characteristics. Supplementary analyses repeated these models using procedures prices for commercial insurance plans. Results For each procedure, list prices varied across counties (intraclass correlation: abdominal ultrasound = 23.2%; colonoscopy = 17.1%; brain MRI = 37.2%; pelvis CT = 50.9%). List prices for each procedure were associated with hospital ownership (all p < 0.001) and percent of population without health insurance (all p < 0.05). For example, list prices for abdominal ultrasound were higher for proprietary versus Government‐owned hospitals (β = 539.10, 95% confidence interval [CI]: 256.12, 822.08, p < 0.001) and for hospitals in counties with more uninsured residents (β = 23.44, 95% CI: 2.55, 44.33, p = 0.03). Commercial insurance prices were negatively associated with metropolitan status. Conclusions Prices for cancer‐related healthcare procedures varied substantially, with considerable heterogeneity associated with county location as well as county‐level social determinants of health (e.g., health insurance coverage). Interventions and policy changes are needed to alleviate the financial burden of cancer care among patients, including geographic variation in prices for cancer‐related procedures.